Public Service Response at the Population Office - Marno Wance; Aslinda Aslinda; Risma Niswaty; Andi Cudai Nur; Alfiana Damasinta (Univiversitas Dr. Djar Wattiheluw, 2024)
Slow and bad administrative services are a phenomenon that people commonly complain about. The responsiveness of public services has become a phenomenon. Public service institutions can provide fast, firm, and uncomplicated services as well as commit and respond to excellent public services. Responsive services are a service model expected to be established in all institutions in Indonesia at the Population and Civil Registry Office of Ambon City. Based on data analysis of NVIVO 12 Plus software analyzing 100 research articles about responsive public services that had been carried out in the previous year, it is found that there is still a lack of Scopus data publication documents published by Indonesian researchers in the theme of responsive public services. The research on the responsive aspect of services has not optimally discussed the aspects of service quality, information technology, organizational culture, work experience, work motivation, lack of facilities, cooperation, and work procedures. Therefore, this study aims at analyzing data from interviews regarding the responsive public services at the Population and Civil Registry Office of Ambon City focusing on these eight aspects using the NVIVO 12 Plus software.